Analisis Perilaku Konsumen di Indonesia Selama Pandemi Covid-19 - Wahyu Lestari; Dian Isnawati; Alvinndo Ichwan Jati (Inspirasi Nusantara, 2022)
The Covid-19 pandemic has had an impact on various fields of human life, including the economy. Consumer behavior is something related to consumer activities starting from searching to purchasing decisions. Of course, the Covid-19 pandemic greatly affects consumer behavior patterns, especially in the aspect of purchasing goods and services. This study aims to determine changes in consumer behavior in the era of the Covid-19 pandemic. This research is a qualitative research with the method of literature review. Data collection techniques are analyzing important information by means of data reduction, data display, and drawing conclusions so as to get an overview of the conclusions regarding the study of literature to be developed in this research. The data analysis used is a systematic literature review technique. The results show that consumer behavior in Indonesia has changed during the Covid-19 pandemic. First, there was panic buying at the start of the Covid-19 pandemic. Second, people are increasingly concerned about health, resulting in an increase in purchasing health products such as masks, multivitamins, medicines, and hand sanitizers as primary goods. Third, people are starting to switch to shopping online to avoid the transmission of Covid-19 in public places. Fourth, people are starting to switch to using e-wallet or digital wallets in the purchase transaction process because it is more practical, safe, fast, and in accordance with health protocols during the Covid-19 pandemic.